Design exploration and kinematic validation of a transtibial prosthesis using a 2SPU-RU parallel mechanism - Abarca, Victoria E. (2025)
This study presents the design exploration and kinematic validation of a transtibial prosthesis based on a 2SPU-RU parallel mechanism. The prototype is currently at Technology Readiness Level 3 (TRL 3), indicating an early-stage concept that has been evaluated under controlled conditions. The mechanism replicates dorsiflexion–plantarflexion, inversion–eversion, and abduction–adduction, corresponding to ankle motion in the sagittal, frontal, and transverse anatomic planes. The system integrates electric actuators and an ESP32 DevKit V1 microcontroller to control joint movements. Functional tests were conducted to assess kinematic performance using inertial sensors and video tracking. Additional evaluations included force distribution analysis using pressure insoles during dorsiflexion and plantarflexion, as well as energy consumption measurements across gait cycles. While the prototype demonstrates the ability to reproduce fundamental gait patterns in a suspended setup, limitations in torque, speed, and control precision restrict its current applicability. These findings provide a foundation for further development. Future work will focus on improving actuator performance, refining control strategies, and extending validation to real-world scenarios and amputee trials.